Pengembangan kegiatan praktikum pemodelan efek rumah kaca untuk siswa SMA pada materi perubahan lingkungan - Rima, Rima; Munandar, Achmad; Anggraeni, Sri (Department of Biology Education, Universitas Pendidikan Indonesia, 2020)
The lack of laboratory equipment and malfunctioning laboratories in schools makes teachers reluctant to carry out practical activities, especially on the topic of environmental change. This study aims to produce an effective practicum activities in accordance with the demands of the curriculum in the elementary school of high school students on the material of global warming. The method if used in this research is descriptive research method. To test the effectiveness of practicum activities developed used a class experiment in class X in a high school by using pretest and posttest. This research uses Thiagarajan et al. (1974) development model that is development model (4-D) (Four-D models). This development model consists of four stages, namely definie, design, develop, without disseminate. The test instrument is a matter of multiple choice with 15 items that have been validated by the expert. The results of the validation show that the greenhouse effect modeling activity, developed in this research is feasible and effective. The effectiveness criteria of the practicum activity refers to the achievement of the average value of the students that exceeds the minimum score (75).